The ultimate guide to internships : 100 steps to get a great internship and thrive in it - Woodard, Eric; Babbitt, Mark. (New York, NY : Allworth Press, 2015)
"Discover the seminal book on turning your internship experience into a career-building launchpad for your future. Author Eric Woodard, who got his start as a star intern in the White House, has mentored hundreds of interns as they transition in their careers to something bigger and better. In these pages he lays out the basics of the internship game, the questions to ask when applying, and the best courses of action for turning an internship into a desirable career. Whether you're still in school, looking for a job after college, or this is your third career change, this guide will give you excellent professional guidance on getting to the next level, expertly covering such topics as: identifying internships that will serve your personal career goals ; distinguishing yourself as an applicant ; knowing what to expect on the job ; impressing your employer and superiors ; networking effectively in the work environment ; preparing yourself for any obstacles ; transitioning to a full-time job ; and many more!"--Amazon.com.
Introduction -- How to get an internship -- How to thrive during your internship -- Conclusion.
Also published with the same ISBN in 2015 by Allworth Press under the author Mark Babbitt and with a different subtitle.
Includes index.
Keywords: Internship programs -- United States -- Handbooks, manuals, etc; Career development -- United States